Persuasive Communication on the " Well Being for Apple (WBA) Psychology Community" in Fostering the Learning Motivation of Port Children (Literasi Nusantara, 2025)
This study aims to examine persuasive communication practices implemented by the Well Being for Apel (WBA) Psychology Community of Trunojoyo Madura University in fostering learning motivation among children in the Kamal Port area, Bangkalan regency. Employing a qualitative intrinsic case study via participatory observation, in-depth interviews, and documentation. The findings indicate that persuasive communication significantly enhances motivation through communicator credibility, engaging delivery, emotional involvement, and positive reinforcement. There are some strategies such as educational games, verbal encouragement, and simple rewards stimulate voluntary participation, while consistent supportive interactions strengthen message acceptance and sustained engagement. The study concludes that persuasive communication is an effective mechanism for nonformal education in socioeconomically limited contexts, offering empirical insights for developing inclusive community learning models.